Causation in insurance contract law - Song, Meixian (Routledge, 2024)
Causation is a crucial and complex matter in ascertaining whether a particular loss or damage is covered in an insurance policy or in a tort claim, and is an issue that cannot be escaped. Now in its second edition, this unique book assists practitioners in answering one of the most important questions faced in the handling of insurance and tort claims. Through extensive case law analysis, this book scrutinises the causation theory in marine insurance and non-marine insurance law, and provides a comparative study on the causation test in tort law. In addition, the author expertly applies causation questions in concrete scenarios, and ultimately, this book provides a single volume solution to a very complex but essential question of insurance law and tort law.